Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To simplify the expression [tex]\(\sqrt[8]{a^4 b^2}\)[/tex], follow these steps:
1. Rewriting the Radicand:
The expression inside the 8th root is [tex]\(a^4 b^2\)[/tex]. Our goal is to simplify this expression under the 8th root.
2. Breaking Down the Exponent:
Recall that [tex]\(\sqrt[n]{x} = x^{\frac{1}{n}}\)[/tex]. Using this property, we can rewrite the 8th root of [tex]\(a^4 b^2\)[/tex] as [tex]\((a^4 b^2)^{\frac{1}{8}}\)[/tex].
3. Applying Exponent Rules:
Apply the exponent rule [tex]\((xy)^n = x^n y^n\)[/tex] to the expression [tex]\((a^4 b^2)^{\frac{1}{8}}\)[/tex]:
[tex]\[ (a^4 b^2)^{\frac{1}{8}} = a^{4 \cdot \frac{1}{8}} \cdot b^{2 \cdot \frac{1}{8}} \][/tex]
4. Simplifying the Exponents:
Now, simplify the exponents:
[tex]\[ a^{4 \cdot \frac{1}{8}} = a^{\frac{4}{8}} = a^{\frac{1}{2}} = \sqrt{a} \][/tex]
[tex]\[ b^{2 \cdot \frac{1}{8}} = b^{\frac{2}{8}} = b^{\frac{1}{4}} = \sqrt[4]{b} \][/tex]
5. Combining the Results:
Combine the simplified expressions:
[tex]\[ (a^4 b^2)^{\frac{1}{8}} = \sqrt{a} \cdot b^{\frac{1}{4}} \][/tex]
Thus, we have:
[tex]\[ \sqrt[8]{a^4 b^2} = \sqrt{a} \cdot b^{\frac{1}{4}} \][/tex]
1. Rewriting the Radicand:
The expression inside the 8th root is [tex]\(a^4 b^2\)[/tex]. Our goal is to simplify this expression under the 8th root.
2. Breaking Down the Exponent:
Recall that [tex]\(\sqrt[n]{x} = x^{\frac{1}{n}}\)[/tex]. Using this property, we can rewrite the 8th root of [tex]\(a^4 b^2\)[/tex] as [tex]\((a^4 b^2)^{\frac{1}{8}}\)[/tex].
3. Applying Exponent Rules:
Apply the exponent rule [tex]\((xy)^n = x^n y^n\)[/tex] to the expression [tex]\((a^4 b^2)^{\frac{1}{8}}\)[/tex]:
[tex]\[ (a^4 b^2)^{\frac{1}{8}} = a^{4 \cdot \frac{1}{8}} \cdot b^{2 \cdot \frac{1}{8}} \][/tex]
4. Simplifying the Exponents:
Now, simplify the exponents:
[tex]\[ a^{4 \cdot \frac{1}{8}} = a^{\frac{4}{8}} = a^{\frac{1}{2}} = \sqrt{a} \][/tex]
[tex]\[ b^{2 \cdot \frac{1}{8}} = b^{\frac{2}{8}} = b^{\frac{1}{4}} = \sqrt[4]{b} \][/tex]
5. Combining the Results:
Combine the simplified expressions:
[tex]\[ (a^4 b^2)^{\frac{1}{8}} = \sqrt{a} \cdot b^{\frac{1}{4}} \][/tex]
Thus, we have:
[tex]\[ \sqrt[8]{a^4 b^2} = \sqrt{a} \cdot b^{\frac{1}{4}} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.